The relevance of Management Control Systems in The Business Environment and The Role of Digitalization in Transformation for Sustainability - A Comprehensive Literature Review - Ayu Fitria Putri; Wahyuni Anggraini; Luk Luk Fuadah (International Journal of Economics Accounting and Management, 2024)
Management Control System (MCS) plays a crucial role in aligning organizational objectives with managerial activities to ensure optimal performance. Over the years, MCS has evolved, integrating new technologies and methodologies to enhance decision-making and accountability within organizations. This paper provides a comprehensive review of recent literature on MCS, with a focus on studies published since 2020. The review highlights key developments in performance measurement, strategic control, and the role of digitalization in MCS. The findings offer valuable insights into the future directions of MCS research and its practical implications in a dynamic business environment.